Effectiveness of group counseling services using self management techniques on aggressive student behavior - Rita Novita; Neviyarni Neviyarni (Universitas Negeri Padang, 2021)
Aggressive behavior is behavior that aims to hurt and injure others physically and psychologically. The factors that influence the occurrence of aggressive behavior are the influence of the student's environment and violent broadcasts on television and social media (Facebook, Instagram, WhatsApp, Telegram and so on). So that efforts are needed to reduce aggressive behavior in students. The aggressive behavior that occurs is physical aggressive behavior, verbal aggressive behavior, excessive angry excessive hostile behavior and behavior. One of the efforts made to reduce students' aggressive behavior at school is to carry out group counseling services with self-management techniques, where the sample in this study was 15 people divided into an experimental group of 8 students and 7 students in the control group. using a non-test instrument, namely a questionnaire. this study aims to test the effectiveness of group counseling services using self-management techniques to reduce aggressive behavior. The findings of this study are: (1) there is a significant difference in the aggressive behavior of the experimental group before and after following self-management techniques (2) there is a significant difference in the aggressive behavior of the control group before and after being given group counseling services about aggressive behavior without special treatment, (3) ) There is a difference in the aggressive behavior of the experimental group students who were given group self-management techniques with the control group who were given group counseling services about aggressive behavior without special treatment, this can be seen in the post-test average score of the experimental group falling higher than the average postest score. control group.